Sources and Chemistry of Flavonoids: An Overview of their Biological and Therapeutic Potential - Hussain, Shabbir; Waqar Mirza; Murtaza, Mufliha; Nazir, Ansa; Hanif, Iram; Ahmad, Muhammad (Scientific Inquiry and Review, 2022)
Flavonoids are natural polyphenolic compounds responsible for the taste and color of medicinal plants, herbs, fruits, and vegetables. Fruits (for example, berries, cherries, plums, apples, lemons, oranges, and grapes) and vegetables (for example., broad beans, olives, onions, spinach, and shallot) are the main sources of flavonoids. They also exist abundantly in cocoa products, black and green tea, red wine, red pepper, chamomile, celery, parsley, ginkgo, and mint. Flavonoid derivatives could also be synthesized through esterification, halogenation, alkoxylation, alkylation, aromatic hydroxylation, acylation, and conjugation with various organic compounds. Flavonoids could also be supplemented as a staple of food which act as a nutraceutical agents and play an important role in the human diet. They possess diverse biological activities including anti-inflammation, anti-oxidation, anti-cancer, anti-diabetes, anti-obesity, antimutagenic, neuroprotective, and also have beneficial effects on oxidative stress, inflammation, insulin resistance, lipid metabolism, and neurodegenerative diseases (for example., amyotrophic lateral sclerosis, Huntington’s disease, Parkinson’s disease and Alzheimer’s disease). Flavonoids contain a 15-carbon skeleton; the basic structure consists of a flavan nucleus, a combination of two benzene and one pyran ring. They are divided into eight important groups namely flavones, flavanols, isoflavones, flavan-3-ols, flavanonols, anthocyanidins, chalcones, and flavanones. A structure-activity relationship exists between flavonoids and their antioxidant activities. Flavonoids are effective in chelating metal ions and scavenging free radicals. Their antioxidant properties are governed by their –OH groups, differences in hydrophobicity, and molecular planarity.